Factors that influence the intent to pursue a master’s degree: evidence from Shandong Province, China - Zhou, Yuhong; Liu, Yi; Xue, Wenhao; Li, Xinyao; Yang, Zhe; Xu, Zhihua (Frontiers in Psychology, 2024)
In recent years, the pursuit of a master's degree has become a social phenomenon of wide concern. It is essential to understand why large number of students choose to pursue master's degree. This study aims to empirically analyze the factors that influence the intent to pursue a master's degree. Method: Based on the extended theory of planned behavior, this study conducts a questionnaire survey of university students in Shandong Province, which has had the highest number of people taking the postgraduate entrance examination in China for several years. A total of 440 questionnaires were finally collected, including 417 valid questionnaires. And then ordinary least squares (OLS) regression was used to analyze the factors that influence the intent to pursue a master's degree. Results: In general, the intent to pursue a master's degree is positively influenced by attitude (β=0.161, p<0.01) and subjective norms (β=0.208, p<0.01), and negatively influenced by risk perception (β=-0.084, p<0.05). Compared with male students, female students' intent is more likely to be influenced by risk perception (β=-0.144, p<0.05) and social factors (β=0.140, p<0.05). The intent of upperclass students tends to be positively influenced by perceived behavioral control (β=0.125, p<0.05), whereas the negative impact of risk perception (β=-0.219, p<0.05) on the intent is significant for underclass students. The intent of students in rural areas are more sensitive to risk perception (β=-0.194, p<0.01) than those of students in cities. In private universities, social factors (β=0.445, p<0.05) significantly affect the intent to pursue a master's degree. In ordinary public universities, the intent of students is more likely to be influenced by risk perception (β=-0.082, p<0.05).The study is helpful to strengthen the understanding of the influencing factors of the intent to pursue a master's degree. In general, the intent to pursue a master's degree is mainly influenced by attitude, subjective norms and risk perception. Moreover, the influencing factors vary among different groups (e.g. female vs. male, rural areas vs. cities). This study can provide policy implications for universities to take targeted educational measures to encourage students to make a choice that suits their own development after graduation.